Awareness, Discovery, Becoming, and Debriefing: Promoting Cross-Cultural Pedagogical Understanding in an Undergraduate Education Program - Johnston, Ingrid; Carson, Terry; Richardson, George; Donald, Dwayne; Plews, John; Kim, Mijung (Alberta Journal of Educational Research, 2009)
This article discusses the first phase of an action research project aimed at identifying a collaborative and collective response to the need to prepare student teachers to work in diverse school contexts. The research brought together university researchers, community and cultural institutions, professional associations, school boards, and government and civil organizations to design a Diversity Institute for integration into the teacher preparation program at the University of Alberta. Student teachers’ responses to the Diversity Institute suggest that although a few participants were able to develop new understandings of themselves and others and to effect changes in their pedagogical practices, many remained at a shallow level of awareness about the complexities of diversity and difference. Reflections on the first phase of the Institute point to the underlying dynamics of learning and unlearning that are at work in becoming a teacher and the need for time and space for a deeper engagement with diversity in the teacher education program.